RISK FACTORS AND MANAGEMENT OF LUNG CANCER IN IDIOPATHIC PULMONARY FIBROSIS: A COMPREHENSIVE REVIEW - Kirkil, Gamze; Mogulkoc, Nesrin; Jovanovic, Dragana (Mattioli 1885, 2025)
. Idiopathic pulmonary fibrosis (IPF) is a fatal lung disease. Lung cancer (LC) is among the most crucial comorbidity factors in patients with IPF. IPF patients that are diagnosed with LC have a reduced mean survival time. Therapeutic strategies for LC in patients with IPF need to be adapted according to the individual treatment risk. Life-threatening acute exacerbation (AE) of IPF may occur in association with cancer treatment, thereby severely restricting the therapeutic options for IPF-associated LC. Because LC and anticancer treatments can worsen the prognosis of IPF, the prevention of LC is as critical as managing patients with IPF.
Keywords: idiopathic pulmonary fibrosis; lung cancer risk; fibrosis-associated lung cancer; management strategies; pulmonary fibrosis and cancer